A manifesto and a response: one hundred years later (Caleidoscopio. Revista de Italianistica de ADILLI, 2026)
One hundred years ago in Italy, with the story of the “two Manifestos”, a fundamental page in Italian political, cultural and intellectual history took place. Gentile’s Manifesto was published in the national press on 21 April 1925 after having decided to draft it during a conference of fascist intellectuals held in Bologna at the end of March. Croce’s Response, which was not intended to be a manifesto, was instead published in the pages of «il Mondo» on 1 May 1925, an anniversary that was not planned from the beginning. Gentile’s text represents a fundamental piece of fascist cultural politics and an absolutely modern conception of culture and the role of intellectuals. Croce’s text, on the other hand, although shining for its style and nobility of intentions, represents a late and losing reaction of liberalism in the face of fascism and a conservative and nineteenth-century conception of culture and the role of intellectuals. A century later, in such a different era and world, it is still useful to remember that episode.
Keywords: culture; intellectual/s; fascism; manifesto; Croce; Gentile